Social and Ubiquitous Technologies for Remote Worker Wellbeing and Productivity in a Post-Pandemic World - Swain, Vedant Das; Saha, Koustuv; Abowd, Gregory; Choudhury, Munmun De (2020)
ABSTRACT In light of the ongoing COVID-19 pandemic, remote work styles have become the norm. However, these work settings introduce new intricacies in worker behaviors. The overlap between work and home can disrupt performance. The lack of social interaction can affect motivation. This elicits a need to implement novel methods to evaluate and enhance remote worker functioning. The potential to unobtrusively and automatically assess such workers can be fulfilled by social and ubiquitous technologies. This paper situates our recent work in the new context by extending our insights for increased remote interaction and online presence. We present implications for proactive assessment of remote workers by understanding day-level activities, coordination, role awareness, and organizational culture. Additionally, we discuss the ethics of privacy preserving deployment, employer surveillance, and digital inequity. This paper aims to inspire pervasive technologies for the new future of work. CCS Concepts: • Human-centered computing → Empirical studies in collaborative and social computing; Empirical studies in ubiquitous and mobile computing; Social media; • Applied computing → Psychology. Keywords future of work, remote work, social media, workplace, worker wellbeing, personnel management, daily activity, routine, role, culture, LinkedIn, Bluetooth, passive sensing ABOUT THE AUTHOR/S Vedant Das Swain Georgia Institute of Technology vedantswain@gatech.edu Vedant Das Swain is a CS Ph.D. student at Georgia Tech, specializing in HCI. He is advised by Gregory D. Abowd and Munmun De Choudhury. His interests lie at the intersection of ubiquitous computing and social wellbeing. [https://vedantswain.com/] Koustuv Saha Georgia Institute of Technology koustuv.saha@gatech.edu Koustuv Saha is a CS Ph.D. candidate at Georgia Tech, specializing in Social Computing. He is advised by Munmun De Choudhury. He studies computational approaches to infer the wellbeing of situated communities with social media. [https://koustuv.com/] Gregory Abowd Georgia Institute of Technology abowd@gatech.edu Munmun De Choudhury Georgia Institute of Technology Munmun.Choudhury@cc.gatech.edu New Future of Work 2020, August 3–5, 2020 © 2020 Copyright held by the owner/author(s).